Structural and gas adsorption characteristics of zeolite adsorbents - Kamarudin, Khairul Sozana Nor (2006)
Gas adsorption on zeolites gains remarkable attention in this new era of nanotechnology since it has industrial importance in many process industries. New technologies involving catalysis, gas separation, gas purification, gas storage, and high temperature gas sensor hold a great promise for industrial applications. In order to develop and design an efficient and economically feasible process, it is important to understand the adsorption characteristics of gas on zeolite. At present, there are many studies have been carried out in the area of gas adsorption, but the data is fragmented and still far from complete. Therefore, the aim of this study is to address some fundamental aspects of gas adsorption by investigating the structural properties and gas adsorption characteristics of different zeolite structures and cations in the extra-framework zeolites. Commercial zeolites representing channel types (ZSM-5, zeolite beta, mordenite, and ferrierite) and cage types (NaX, NaY, and zeolite A) were used in order to study the effect of structural arrangement on gas adsorption. Synthesized zeolite Y (Na-SZ18) was also used as comparison to NaY commercial, and for modification study. Modification using cation exchange method was carried out on the cage-type zeolite (Na-SZ18) by exchanging Na+ with other cations namely Li+, K+, and Rb+ (alkali metals), Mg2+, Ca2+, and Ba2+ (alkaline earth metals), and Mn2+, Ni2+, and Zn2+ (transition metals). Methane and carbon dioxide, the main components of natural gas, were used as adsorbates. The physical and chemical properties of zeolite adsorbents were determined using x-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier Transform infra-red (FTIR) spectroscopy techniques, and nitrogen adsorption at 77 K. Gas adsorption measurements were carried out using volumetric and gravimetric methods. Gas adsorption characteristics of zeolites were evaluated based on the adsorption capacity, adsorption isotherms, heat of adsorption, uptake rate of the adsorbates, and FTIR spectra of gas-zeolite interactions. It was found that cage-type zeolites are better adsorbents than channel-type zeolites. The adsorption of methane on Na-SZ18 is 5 times higher while the adsorption of carbon dioxide is 4 times higher than ferrierite. The gas adsorption measurements also revealed that exchanging Na+ with some metal cations enhanced the adsorption capacity of methane (19.8 %) and carbon dioxide (7.48 %) on modified zeolites. In addition, FTIR spectroscopy results also suggested that the extra-framework cation influenced the interaction between adsorbates and the zeolite surface. Finally, the mechanisms of gas adsorption were proposed based on zeolite of different structures and metal cations. All these results suggests that structural properties and the cations that present in extra-framework zeolites affect the adsorption characteristics of methane and carbon dioxide on zeolites.